A zirconium-based metal-organic framework material for solid-phase microextraction of trace polybrominated diphenyl ethers from milk. (1st July 2020) - Jiang, Hai-Long; Li, Na; Wang, Xia; Wei, Xiang-Yu; Zhao, Ru-Song; Lin, Jin-Ming
Highlights: UiO-66-OH material was applied for the first time in food analysis. Response surface methodology was introduced to optimize adsorption conditions. The method was effective to determine trace PBDEs in milk. Possible adsorption mechanism was deduced for further development of the method. Abstract: A zirconium-based metal-organic framework material (UiO-66-OH) was designed and applied for the first time as an adsorbent in food analysis for the solid phase microextraction of trace polybrominated diphenyl ethers (PBDEs) from milk. The materials were characterized by powder X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analyses. Through response surface methodology, the optimal conditions for adsorption were determined to as follows: extraction time of 30 min, ionic strength of 15%, extraction temperature of 61 °C, and stirring speed of 880 r/min. Under the optimal conditions, the method showed excellent linearity with a high correlation coefficient ( r ≥ 0.9994), low limits of detection in the range of 0.15–0.35 ng L −1, good interday precision ranging of 7.58%-9.48%, and satisfactory recoveries of 74.7%-118.0%. All these findings showed that the method was reliable and effective for detecting trace PBDEs in milk.